ANALYSIS OF FACTORS AFFECTING THE REGIONAL POVERTY GAP INDEX - Mukhtar, Saparuddin; Suparno; Safhira, Tyas (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The poverty gap index is a measure of poverty that emphasizes the average expenditure gap against the poverty line. This study aims to propose theoretical modelling of how the poverty gap index can approach the poverty line or in other words, the gap is getting smaller. The theory used in this research is the theory of the vicious circle of poverty as well as through the theory of economic growth. The factors that influence the poverty gap index analyzed and identified are the dependency ratio, mean years of schooling, and gross domestic product at constant prices. This research method uses a qualitative approach with literature study techniques, by analyzing theories and previous research and determining factors as predictors of poverty problems. Grounded theory by comparing correlation results as the findings of this research. This study shows that the dependency ratio has a positive effect on the poverty gap index, while the mean years of schooling and gross regional domestic product have a negative effect on the poverty gap index. Recommendations for future research, researchers suggest using other measurement indicators in poverty or other research methods to add or support similar research references.